2015
DOI: 10.2196/resprot.4363
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Mediators, and Effect Predictors of Internet Interventions for Chronic Cancer-Related Fatigue: The Design and an Analysis Plan of a 3-Armed Randomized Controlled Trial

Abstract: BackgroundInternet interventions offer advantages that especially cancer survivors who suffer from fatigue could benefit from. Given the growing number of such patients, Internet interventions could supplement and strengthen currently available health care.ObjectiveThis paper describes the design and analysis plan that will be used to study 2 Internet interventions aimed at reducing severe fatigue in cancer survivors: a mobile ambulant activity feedback therapy supported through a weekly email by a physiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 97 publications
(91 reference statements)
0
45
0
Order By: Relevance
“…7 This intervention currently is being tested in an RCT, but to our knowledge the results have not been published to date. 8 Another relevant, ongoing RCT concerns a pilot study by Corbett et al examining an online selfmanagement intervention with CBT elements. 9 Finally, 2 RCTs by Willems et al 10 and van den Berg et al 11 demonstrated that a general Web-based self-management intervention for psychosocial adjustment in cancer survivors (without a specific focus on fatigue) led to improvements in fatigue compared with a nonactive control group, with small effect sizes (Cohen's d of 0.2 and 0.3, respectively).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…7 This intervention currently is being tested in an RCT, but to our knowledge the results have not been published to date. 8 Another relevant, ongoing RCT concerns a pilot study by Corbett et al examining an online selfmanagement intervention with CBT elements. 9 Finally, 2 RCTs by Willems et al 10 and van den Berg et al 11 demonstrated that a general Web-based self-management intervention for psychosocial adjustment in cancer survivors (without a specific focus on fatigue) led to improvements in fatigue compared with a nonactive control group, with small effect sizes (Cohen's d of 0.2 and 0.3, respectively).…”
Section: Original Articlementioning
confidence: 99%
“…A randomized controlled trial (RCT) by Yun et al 5 demonstrated that a Web-based self-management education program led to greater improvements in fatigue in cancer survivors compared with care as usual (CAU). 8 Another relevant, ongoing RCT concerns a pilot study by Corbett et al examining an online selfmanagement intervention with CBT elements. However, this effect was not sustained at a follow-up of 12 weeks, and no positive effect on fatigue severity was found.…”
Section: Introductionmentioning
confidence: 99%
“…Published protocols of clinical trials [74][75][76][77][78][79][80][81] involving wearable activity monitors in cancer populations are listed in Supplementary Table 2. The most commonly reported device among protocols is the triaxial GT3X + accelerometer (n = 3) [76,79,81].…”
Section: Current Protocolsmentioning
confidence: 99%
“…The most commonly reported device among protocols is the triaxial GT3X + accelerometer (n = 3) [76,79,81]. Other trial designs include the use multisensor systems paired with smart phone applications (n = 2) [79,80], pedometers/step counters (n = 2) [74,77], and other accelerometers (n = 2) [75,78], and two trials plan to use more than one device [77,79].…”
Section: Current Protocolsmentioning
confidence: 99%
“…Feedback on physical activity was provided on the device itself, and also on the screen of the mobile phone, using the Activity Coach application. This application is a re-design of the application developed by Roessingh Research and Development and tested with several clinical populations, such as cancer survivors (Wolvers et al 2015) and patients suffering from chronic pulmonary obstructive disease (Tabak et al 2014). In the mobile phone, participants received feedback on the number of steps at that moment, number of steps at the current day per hour and during the last week per day.…”
Section: Measurementsmentioning
confidence: 99%